The first Irish cities : an eighteenth-century transformation - Dickson, David, 1947- (Yale University Press, 2021)
A backward corner of Europe in 1600, Ireland was transformed during the following centuries. This was most evident in the rise of its cities, notably Dublin and Cork. David Dickson explores ten urban centers and their patterns of physical, social, and cultural evolution, relating this to the legacies of a violent past, and he reflects on their subsequent partial eclipse. Beautifully illustrated, this account reveals how the country's cities were distinctive and-through the Irish diaspora-influential beyond Ireland's shores.